Theoretical prediction of sandwiched two-dimensional phosphide binary compound sheets with tunable bandgaps and anisotropic physical properties. (25th January 2018) - Zhang, C Y; Yu, M
Abstract: Atomic layers of GaP and InP binary compounds with unique anisotropic structural, electronic and mechanical properties have been predicted from first-principle molecular dynamics simulations. These new members of the phosphide binary compound family stabilize to a sandwiched two-dimensional (2D) crystalline structure with orthorhombic lattice symmetry and high buckling of 2.14 Å–2.46 Å. Their vibration modes are similar to those of phosphorene with six Raman active modes ranging from ∼80 cm −1 to 400 cm −1 . The speeds of sound in their phonon dispersions reflect anisotropy in their elastic constants, which was further confirmed by their strong directional dependence of Young's moduli and effective nonlinear elastic moduli. They show wide bandgap semiconductor behavior with fundamental bandgaps of 2.89 eV for GaP and 2.59 eV for InP, respectively, even wider than their bulk counterparts. Such bandgaps were found to be tunable under strain. In particular, a direct–indirect bandgap transition was found under certain strains along zigzag or biaxial orientations, reflecting their promising applications in strain-induced bandgap engineering in nanoelectronics and photovoltaics. Feasible pathways to realize these novel 2D phosphide compounds are also proposed.